Some Afrotropical species of Atherigona Rondani (Diptera: Muscidae) revisited and a new species described - Deeming, John C. (European Journal of Taxonomy, 2022)
New taxonomic data on some species of Atherigona Rondani are provided. This is partly based on recently discovered types of A. laevigata (Loew), A. maculipennis Stein, A. magnipalpis Stein, A. nigrithorax Stein and A. subnigripes (Karsch), and partly on new material that has become available. Among this new material is a new species here described: Atherigona zongoi sp. nov. The newly discovered types of Atherigona nigrithorax Stein and A. subnigripes (Karsch) are redescribed. The status of a specimen of Coenosia humeralis found among material in the Smithsonian Institution and incorrectly labelled as the type of Atherigona humeralis is clarified. The puparium of A. varia (Meigen) is partially described for the first time. New records are given for several species and distribution is updated.